Bile Salt-Stimulated Lipase Activity in Donor Breast Milk Influenced by Pasteurization Techniques - Koh, Jeewon; Victor, Ashley F.; Howell, Matthew L.; Yeo, Jooyoung G.; Qu, Yunyao; Selover, Brandon; Waite-Cusic, Joy; Dallas, David C. (Frontiers in Nutrition, 2020)
Breast milk contains bile salt-stimulated lipase (BSSL), which significantly increases the fat digestion capacity of newborns who have limited pancreatic lipase secretion in the first few months after birth. Problematically, Holder pasteurization used in non-profit milk banks to ensure the microbiological safety of donor milk for infants, particularly preterm infants (<37 weeks gestation age), destroys milk BSSL, thus limiting infant fat absorption capacity. Alternative strategies are needed to ensure the safety of donor milk while preserving BSSL activity. Three alternative pasteurization techniques—high-pressure processing (HPP, 550 MPa, 5 min), gamma cell irradiation (IR, 2.5 Mrads) and UV-C (254 nm, 0–33,000 J/L)—were compared with Holder pasteurization (low-temperature long-time, LTLT, 62.5°C, 30 min) for retention of BSSL activity in donor breast milk. As the time required for donor milk pasteurization by UV-C in published methods was not clear, donor breast milk was spiked with seven common bacterial strains and treated by UV-C for variable time periods and the minimum UV-C dosage required to achieve a 5-log10 reduction of CFU/mL was determined. Eight thousand two hundred fifty J/L of UV-C exposure was sufficient to achieve 5-log10 reduction of each of bacterial targets, including Bacillus and Paenibacillus spores. The retention of BSSL activity was highest after HPP (retaining 62% of the untreated milk BSSL activity), followed by UV-C (16,500 J/L), IR and LTLT (35, 29, and 0.3% retention, respectively). HPP was an effective alternative to pasteurize milk with improved retention of BSSL activity compared to Holder pasteurization. Future work should investigate the effect of alternative pasteurization techniques on the entire array of bioactive components in donor breast milk and how these changes affect preterm infant health outcomes. Implementation of HPP technique at milk banks could improve donor milk-fed infant fat absorption and growth.